Artificial gap creation and the saproxylic beetle community - Bodin, Nils (2016)
Coarse dead wood (CWD) and gaps are structures that have become sparse in Swedish forests as a result of forestry. This is believed to be one factor contributing to diminishing biodiversity. Because of political undertakings to preserve biodiversity, Swedish agencies and forestry companies now aim to restore these and other structures. To do so prescribed measures of nature conservation are today being practiced. One such measure is artificial gap creation. This study analyzes the effects of this measure on saproxylic beetle communities. The measure involve the cutting of several gaps per hectare and stand, as well as creating four CWD substrates in several gaps: Tipped trees, cut trees, girdled trees and high stumps. Data was collected from substrate traps as well as on substrate- and stand properties. In this study the effects that different substrate properties have on the abundance and species richness of the saproxylic beetle community were analyzed. GLMM-models were constructed for each of the two response variables, using several explanatory variables. Results indicate that abundance was most affected by the type of substrate, while species richness was most affected by its positive relationship to substrate diameter. The difference in abundance between substrate types could indicate that different species breed in different substrates. The positive effect that increased diameter have on species richness could be a result of how a larger substrate house larger communities of beetles – but since substrate diameter had no significant effect on abundance it could also indicate differences in inter-species substrate preferences.